Study of the possibility of introduction of Kazakhstan NGO-based rapid HIV testing procedures - Alibayeva KO (Dove Medical Press, 2019)
KO Alibayeva,1 MK Saparbekov,1 BS Baiserkin,2 AT Abishev,2 GH Tazhibaeva,2 SZ Kasymbekova2 1Department of Public Health and Social Sciences, Kazakhstan School of Public Health, Kazakhstan Medical University, Almaty, Republic of Kazakhstan; 2Organization and Methodical Department, Reference Laboratory, Republican Center on Prevention and Control of AIDS, Almaty, Republic of KazakhstanCorrespondence: KO AlibayevaKazakhstan’s Medical University “Kazakhstan School of Public Health”, 19A Utepov Street, Almaty 050060, Republic of KazakhstanTel +7 701 778 6509Email karlygash-2303@mail.ruIntroduction: New initiatives presented by the World Health Organization (WHO) and the Joint United Nations Program on HIV and AIDS , such as 90-90-90, test and treat, preventive treatment, and best international practices related to the introduction of rapid human immunodeficiency virus (HIV) testing in clinics, and field conditions, including self-testing, predetermined the introduction of NGO-based rapid HIV testing in the Republic of Kazakhstan nongovernmental organizations (NGOs). This work presents the results of a comprehensive study conducted about the possible introduction of NGO-based rapid HIV testing in the country. It should be noted that 32,573 HIV infections have been diagnosed in Kazakhstan (prevalence of 117.7 per 100,000 people) from 1987 to 2018. Most of these new cases are diagnosed among “key” population groups, such as people who use injectable drugs, sex workers, men who have sex with men, those who rely mainly on NGOs, and those who prefer to deal with an organization such as an NGO, which makes it possible to introduce NGO-based rapid HIV testing in Kazakhstan.Methods: In this work, we used the following rapid HIV tests: Alere DetermineTM HIV ½ Ag/Ab Combo, Hexagon HIV 1+2, Abon HIV ½, HIV 1,2 Han Medtest, and Geenius HIV1/2 Confirmatory.Results: The study of the rapid tests, including their diagnostic patterns, conducted in Kazakhstan shows that five rapid HIV tests completely meet the WHO’s requirements (sensitivity>99%; specificity>98%). These are Alere DetermineTM HIV ½ Ag/Ab Combo, Hexagon HIV 1+2, Abon HIV ½, HIV 1,2 Han Medtest, and Geenius HIV1/2 Confirmatory. The study of legal and social problems associated with rapid HIV testing in NGOs shows that HIV-related medical examination and counseling carried out in Kazakhstan, including those by rapid methods, are governed by corresponding laws and normative legal documents.Conclusion: It has been established that there are social barriers that interfere with rapid HIV testing. In view of this, services associated with NGO-based rapid HIV testing shall be rendered with the use of a social and legal protection mechanism for those under examination.Keywords: rapid HIV testing, NGO, key population groups, HIV infection, Republic of Kazakhstan